The conceptual humanizing entrepreneurship programme: creating job opportunities for the unemployed youth and to reduce poverty in Kediri, East Java - Pratama, Muhammad Wahyu Rizqi; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
One of the main problems facing the Indonesian nation and state is the problem of unemployment. High unemployment has a high impact on poverty, unemployment in Indonesia is a problem that cannot be resolved. Unemployment in Indonesia is dominated by youth which is 13.47% and the largest spread of youth is on the island of Java 55.53%, this is due to several factors including the size of the workforce that is not balanced with employment opportunities and the level of education and skills possessed by Indonesian people very low through the literature review from 2011-2018, there were significant results on the effect of providing entrepreneurial education on entrepreneurial interests. For this conceptual paper has a program based on the objectives of the SDGs, this program is a Smart Entrepreneur which is an educational program and practice on entrepreneurship aimed at unemployed youth in the Kediri area of East Java, this program has the potential to (a) improve the regional economy, (b) improve community social status, (c) shape the character of entrepreneurship based on Islamic religious values of hard work, honesty, high creativity and leadership, (d) able to open their own jobs and be able to teach knowledge to other communities. This program is developed based on the Business Model Canvas (BMC) approach which looks at the customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. The application of the BMC in this paper is expected to illustrate the conceptual solution that will be carried out later.